Biodiesel glycerin valorization into oxygenated fuel additives - Soares Dias, A. P. (2021)
requires costly purification before commercialization. Production of oxygenated fuel additives is a potential route for glycerin valorization. Glycerin acetylation was carried out over heterogeneous acid catalysts (15%, glycerol weight basis) using glacial acetic acid (molar ratio=9). The catalysts, containing different amounts of phosphate species (P/Si from 10 to 20 atomic ratio), were prepared by wet impregnation of commercial silica with aqueous solutions of diammonium phosphate and ortho-phosphoric acid. X-ray diffraction patterns of calcined solids presented amorphous patterns like raw silica. The prepared catalysts presented, at 120 degrees C, glycerol conversion higher than 89.5% after 1 h of reaction, been diacetin the major product, with triacetin selectivities lower than 26.1%. Diacetin selectivity was found to be almost invariant with catalyst acidity thus underlining the relevance of catalyst porosity due to the large acetins molecules sizes. The slow rate of triacetin diffusion in narrow pores of catalyst might be responsible for the relatively low yield obtained. Surface phosphate species showed a slow rate of leaching in the reaction medium showing high catalyst stability.